Resin composition and method for preparing resin composition
By introducing block copolymer domain regions with specific sizes and distributions into the polyolefin resin, the problem of insufficient impact resistance of the polyolefin resin at room temperature and low temperature is solved, and the excellent mechanical properties and processability of the resin composition are achieved.
Patent Information
- Application Number
- CN202380060014.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-11-03
- Publication Date
- 2025-03-28
AI Technical Summary
Polyolefin resin compositions such as polypropylene have insufficient impact resistance at room temperature and low temperatures. The prior art uses styrene-ethylene-butene-styrene (SEBS) block copolymers, but are costly and have limited effects.
A resin composition is developed that includes a matrix region and a plurality of domain regions dispersed in the matrix region, the domain region contains a block copolymer composed of aromatic vinyl polymer blocks and olefin polymer blocks, and the size of the domain region and the distance between the multiple domain regions is controlled between about 10 nm to 15 nm and 20 nm to 60 nm, respectively.
The impact resistance of the resin composition at room temperature and low temperature is significantly improved, providing excellent mechanical properties and processability.
Smart Images

Figure BDA0005272439060000111 
Figure BDA0005272439060000121 
Figure BDA0005272439060000122
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0145764 filed in the Korean Intellectual Property Office on November 4, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The present invention relates to a resin composition comprising a multi-block copolymer and a preparation method thereof. Background Art
[0005] Polypropylene has excellent rigidity and molding processability, and is therefore widely used as a medical material. However, polypropylene has a problem of weak impact strength, and in order to compensate for this, a method of using a styrene-based thermoplastic elastomer, that is, a styrene-ethylene-butylene-styrene (SEBS) block copolymer as an elastomer in a polypropylene resin composition has been proposed.
[0006] However, SEBS is expensive and has a limited effect on improving the low-temperature impact strength of polypropylene resin compositions. Therefore, SEBS is not suitable for use as a medical material mainly used in low-temperature environments.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: KR 10-1657925B1 Summary of the invention
[0010] Technical issues
[0011] An object of the present invention is to improve the room temperature and low temperature impact resistance of polyolefin resin compositions such as polypropylene.
[0012] That is, an object of the present invention is to provide a polyolefin resin composition having improved impact resistance at both room temperature and low temperature and a method for preparing the same.
[0013] Technical Solution
[0014] According to one aspect of the present invention, a resin composition and a preparation method thereof are provided.
[0015] (1) The present invention provides a resin composition comprising: a matrix region; and a plurality of domains dispersed in the matrix region; wherein the matrix region comprises a polyolefin resin, the domains comprise a block copolymer, the block copolymer comprises an aromatic vinyl polymer block and an olefin polymer block, the size of the domains is about 10 nm to about 15 nm, and the distance between the plurality of domains is about 20 nm to about 60 nm.
[0016] (2) In the above (1), the present invention provides a resin composition, wherein the domain has a spherical or ellipsoidal shape.
[0017] (3) In the above (1) or (2), the present invention provides a resin composition, wherein the polyolefin resin is polypropylene.
[0018] (4) In any one of the above (1) to (3), the present invention provides a resin composition, wherein the olefin polymer block comprises an ethylene monomer unit and an α-olefin monomer unit.
[0019] (5) In any one of the above (1) to (4), the present invention provides a resin composition, wherein the olefin polymer block comprises an ethylene monomer unit and a C3-C20 α-olefin monomer unit.
[0020] (6) In the above (4) or (5), the present invention provides a resin composition, wherein the α-olefin monomer is one or more selected from the group consisting of 1-propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene and 3,4-dimethyl-1-hexene.
[0021] (7) In the above (4) to (6), the present invention provides a resin composition, wherein the resin composition contains a polyolefin resin in an amount of about 40 wt % to about 80 wt % and a block copolymer in an amount of about 20 wt % to about 60 wt %.
[0022] (8) The present invention provides a method for preparing a resin composition, which comprises: (S10) polymerizing one or more olefin monomers in the presence of a chain transfer agent by using a catalyst composition comprising a transition metal catalyst to prepare an olefin polymer block intermediate; (S20) introducing an initiator and an aromatic vinyl monomer and polymerizing them in the presence of the olefin polymer block intermediate prepared in step S10 to prepare a block copolymer; and (S30) blending the block copolymer prepared in step S20 with a polyolefin resin S30.
[0023] (9) In the above (8), the present invention provides a method for preparing a resin composition, wherein the catalyst composition comprises an aluminoxane compound and a trialkylaluminum.
[0024] (10) In the above (9), the present invention provides a method for preparing a resin composition, wherein the trialkylaluminum is trioctylaluminum.
[0025] (11) In the above (9), the present invention provides a method for preparing a resin composition, wherein the catalyst composition comprises an aluminoxane compound and a trialkylaluminum in a molar ratio of 1:0.01 to 10.0.
[0026] Beneficial Effects
[0027] The resin composition of the present invention is excellent in both room temperature and low temperature impact resistance. DETAILED DESCRIPTION
[0028] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention.
[0029] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should also be understood that based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the present invention, the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant field and the technical concept of the present invention.
[0030] In the present invention, the term "monomer unit" may refer to a component, structure or material itself derived from a monomer, and as a specific example, may refer to a repeating unit formed in a polymer due to participation of an introduced monomer in a polymerization reaction when polymerizing a polymer.
[0031] The term "polymer" used in the present invention may refer to a homopolymer formed by polymerization from a single type of monomer, and a "copolymer" may refer to a copolymer formed by polymerization of two or more types of monomers. In addition, unless otherwise indicated as a "block", a "copolymer" may refer to a "random copolymer" obtained by random copolymerization of two or more types of monomers.
[0032] The term "block" used in the present invention may refer to a group of repeating units consisting only of repeating units derived from the same monomer or only of repeating units derived from the same comonomer, because only the same monomer or only the same comonomer participates in the polymerization reaction in the copolymer, and as a specific example thereof, an aromatic vinyl polymer block may refer to a block formed only of aromatic vinyl monomer units, and an olefin polymer block may refer to a block formed only of more than one olefin monomer units.
[0033] The term "anionic living polymer" used in the present invention is a polymer formed by anionic polymerization, and may refer to a polymer capable of further polymerizing or reacting by maintaining an anionic state at one end of the polymer, and as a specific example, may refer to a living anionic polymer.
[0034] The term "composition" used in the present invention includes not only reaction products and decomposition products formed from the materials of the corresponding composition, but also includes a mixture containing the materials of the corresponding composition.
[0035] The invention provides a resin composition.
[0036] According to one embodiment of the present invention, the resin composition comprises: a matrix region; and a plurality of domains dispersed in the matrix region; wherein the matrix region comprises a polyolefin resin, the domains comprise a block copolymer, the block copolymer comprises an aromatic vinyl polymer block and an olefin polymer block, the size of the domains is about 10 nm to about 15 nm, and the distance between the plurality of domains is about 20 nm to about 60 nm.
[0037] According to one embodiment of the present invention, the domain region can be a dispersed phase dispersed in a continuous phase, and at this time, the domain region can be a dispersed phase dispersed in the continuous phase of the matrix region in the shape of a sphere or an ellipsoid. In other words, the domain region can be dispersed in the matrix region in the shape of a sphere or an ellipsoid.
[0038] According to one embodiment of the present invention, if the domain is a sphere, the "size" in the size of the domain may refer to the diameter of the sphere. In addition, if the domain is an ellipsoid, the "size" in the size of the domain may refer to the length of the longest axis of three pairs of perpendicular symmetry axes intersecting at the symmetry center of the ellipsoid. In addition, the size of the domain may refer to the individual size of each domain in a plurality of domains, or may refer to the arithmetic average size of the sizes of a plurality of domains.
[0039] According to one embodiment of the present invention, the size of the domain can be about 10 nm to about 15 nm. As a specific example, the size of the domain can be about 10.0 nm or more, about 10.1 nm or more, about 10.2 nm or more, about 10.3 nm or more, about 10.4 nm or more, about 10.5 nm or more, about 10.6 nm or more, about 10.7 nm or more, about 10.8 nm or more, about 10.9 nm or more, about 11.0 nm or more, about 11.1 nm or more, about 11.2 nm or more, about 11.3 nm or more, about 11.4 nm or more, about 11.5 nm or more, about 11.6 nm or more, or about 11.7 nm or more, and can also be about 15.0 nm or less, about 14.9 nm or less, about 14.8 nm or less, about 14.7 nm or less, about 14.6 nm or less, or about 14.5 nm or less. The size of the domain is used to show the dispersion form, such as the dispersion degree of the domain in the polyolefin resin dispersed in the matrix region, and as mentioned above, if the size of the domain in the resin composition is controlled, the dispersion degree of the block copolymer of the domain dispersed in the polyolefin resin in the matrix region can be controlled, thereby improving the impact strength of the resin composition.
[0040] According to one embodiment of the present invention, the distance between multiple domains may refer to the distance between each domain existing in the matrix region, and specifically may refer to the distance between the closest points among the outermost points of multiple domains, wherein each domain is shaped as a sphere or an ellipsoid. In addition, the distance between multiple domains may refer to a single distance between multiple domains, or may refer to the arithmetic average distance of the distances between multiple domains.
[0041] According to one embodiment of the present invention, the distance between the multiple domains can be about 20nm to about 60nm. As a specific example, the distance between the multiple domains can be about 20.0nm or more, about 21.0nm or more, about 22.0nm or more, about 23.0nm or more, about 24.0nm or more, about 25.0nm or more, about 26.0nm or more, about 27.0nm or more, about 28.0nm or more, about 29.0nm or more, about 30.0nm or more, about 31.0nm or more, about 32.0nm or more, about 32.1nm or more, about 32.2nm or more, about 32.3nm or more , about 32.4nm or more, about 32.5nm or more, about 32.6nm or more, about 32.7nm or more, or about 32.8nm or more, and may also be about 60.0nm or less, about 55.0nm or less, about 50.0nm or less, about 49.0nm or less, about 48.0nm or less, about 47.0nm or less, about 46.0nm or less, about 45.0nm or less, about 44.0nm or less, about 43.0nm or less, about 42.0nm or less, or about 41.3nm or less. The distance between multiple domains is used to show the dispersion form, such as the dispersion degree of the domains in the polyolefin resin dispersed in the matrix region, and as described above, if the distance between multiple domains in the resin composition is controlled, the dispersion degree of the block copolymer in the domain dispersed in the polyolefin resin in the matrix region can be controlled, thereby improving the impact strength of the resin composition.
[0042] According to one embodiment of the present invention, in the resin composition, it is important that the size of the domain and the distance between the multiple domains are controlled separately, but it is also important that the size of the domain and the distance between the multiple domains are controlled within the above range at the same time. As described above, when the size of the domain and the distance between the multiple domains are controlled within the above range at the same time, the impact strength of the resin composition can be further improved. At the same time, at least two or more domains can be present in the matrix region, so as to meet the size of the domain, the distance between the multiple domains and the ratio of the content of the matrix region to the domain. In addition, the size of the domain and the distance between the multiple domains can be controlled by a block copolymer containing an aromatic vinyl polymer block and an olefin polymer block in the domain.
[0043] According to one embodiment of the present invention, the size of a domain and the distance between multiple domains can be measured by small angle X-ray scattering (SAXS) analysis. Specifically, small angle X-ray scattering analysis can be used to identify the microstructure and morphology of polymers and / or copolymers in the domains in the resin composition. According to small angle X-ray scattering analysis, by indexing, it is possible to predict which phase the polymer in the domain of the resin composition exists in, and if fitting is performed by assuming a model for the diffraction peak of the small angle X-ray scattering analysis pattern, the structural information of the polymer, such as the domain size in a specific phase and the distance between the domains, can be obtained. In addition, the size of the domain and the distance between multiple domains can be measured by transmission electron microscopy (TEM) analysis. At this point, small angle X-ray scattering analysis and transmission electron microscope images can be analyzed together to more clearly identify the morphology of polymers in the domain.
[0044] According to one embodiment of the present invention, the polyolefin resin may be polypropylene, which may be a polypropylene homopolymer or a copolymer of propylene and an α-olefin monomer, wherein the copolymer may be an alternating, random or block copolymer.
[0045] According to one embodiment of the present invention, in polypropylene, the α-olefin monomer can be specifically C2-C12 or C2-C8 aliphatic olefin. More specifically, examples thereof can be ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene, 3,4-dimethyl-1-hexene, etc., and any one or a mixture of two or more thereof can be used.
[0046] According to one embodiment of the present invention, the polypropylene may be any one or a mixture of two or more selected from the group consisting of polypropylene homopolymer, propylene-α-olefin copolymer and propylene-ethylene-α-olefin copolymer, and the copolymer is a random or block copolymer.
[0047] According to one embodiment of the present invention, the melt index (MI) of the polypropylene measured at 230°C and a load of 2.16kg according to ASTM D1238 can be about 0.5g / 10min to about 100g / 10min, about 0.5g / 10min or more, or about 1.0g / 10min or about 2.0g / 10min or more, and can also be about 100g / 10min or less, about 90g / 10min or less, or about 50g / 10min or less, and within this range, processability can be further improved during injection molding of the resin composition. In addition, the polypropylene can be a copolymer having the above-mentioned melt index, and can specifically be a propylene-ethylene copolymer or a high crystalline polypropylene (HCPP), in which case the strength properties can be further improved.
[0048] According to one embodiment of the present invention, the polypropylene may have a DSC melting point of about 120°C to about 160°C.
[0049] According to one embodiment of the present invention, in order to meet the above physical property requirements, polypropylene can be prepared using a typical polymer preparation reaction, or polypropylene can be commercially obtained and used. A specific example thereof can be SEETEC manufactured by LG Chem Co. TM M1600, CB5230 manufactured by Korea Oil & Chemical Co., and SFC-750D manufactured by Lotte Chemical Co. In addition, the polypropylene may be a random propylene copolymer, which may be Braskem manufactured by Brakem America Inc. TM PP R7021-50RNA, or Formolene manufactured by Formosa Plastics Corporation TM 7320A.
[0050] According to one embodiment of the present invention, the block copolymer including the aromatic vinyl-based polymer block and the olefin-based polymer block is a multi-block copolymer, which can be prepared in the presence of a novel additive as described in the method for preparing the resin composition described later.
[0051] According to one embodiment of the present invention, the weight average molecular weight of the block copolymer can be about 100000 g / mol to about 300000 g / mol, and as a specific example, it can be about 100000 g / mol or more, about 110000 g / mol or more, about 120000 g / mol or more, or about 125000 g / mol or more, and can also be about 300000 g / mol or less, about 290000 g / mol or less, about 280000 g / mol or less, about 270000 g / mol or less, about 260000 g / mol or less, about 250000 g / mol or less, about 240000 g / mol or less, about 230000 g / mol or less, about 220000 g / mol or less, about 210000 g / mol or less, or about 200000 g / mol or less.
[0052] According to one embodiment of the present invention, the molecular weight distribution (PDI) of the block copolymer can be about 1.5 to about 3.0, and as a specific example, it can be about 1.5 or more, about 1.6 or more, about 1.7 or more, about 1.8 or more, about 1.9 or more, about 2.0 or more, about 2.1 or more, about 2.2 or more, about 2.3 or more, or about 2.4 or more, and can also be about 3.0 or less, about 2.9 or less, about 2.8 or less, about 2.7 or less, about 2.6 or less, or about 2.5 or less. Here, molecular weight distribution is calculated by the ratio of "weight average molecular weight / number average molecular weight", and weight average molecular weight and number average molecular weight are polystyrene conversion molecular weights analyzed by gel permeation chromatography (GPC).
[0053] According to one embodiment of the present invention, the block copolymer may be a block copolymer in which the olefin-based polymer block includes a side chain derived from a main chain.
[0054] According to one embodiment of the present invention, the aromatic vinyl polymer block may be a block formed by polymerization of an aromatic vinyl monomer, and the aromatic vinyl monomer used to form the aromatic vinyl polymer block may be one or more selected from the group consisting of styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene and 1-vinyl-5-hexylnaphthalene, and as a specific example, it may be styrene.
[0055] According to one embodiment of the present invention, the content of the aromatic vinyl polymer block relative to the total content of the block copolymer can be about 10 wt % to about 60 wt %, about 15 wt % to about 40 wt %, or about 20 wt % to about 35 wt %, and within this range, there is an effect of excellent mechanical properties and processability of the block copolymer.
[0056] According to one embodiment of the present invention, olefin polymer block may include ethylene monomer unit and alpha-olefin monomer unit.As a specific example, olefin polymer block (i.e., poly (ethylene-co-olefin)) may include ethylene monomer unit and C3-C20 alpha-olefin monomer unit, and as a specific example, may include ethylene monomer unit and C6-C8 alpha-olefin monomer unit.As described above, if olefin polymer block includes ethylene monomer unit and C3-C20 or C6-C8 alpha-olefin monomer unit, weather resistance, heat resistance, wear resistance, impact resistance, adhesion, transparency and recyclability are excellent, and there is an effect that the mechanical properties of the resin composition including block copolymer are improved.Meanwhile, the ethylene monomer unit and alpha-olefin monomer unit of olefin polymer block may be present in olefin polymer block in the form of random copolymer.
[0057] According to one embodiment of the present invention, the α-olefin monomer forming the α-olefin monomer unit may be one or more selected from the group consisting of 1-propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene and 3,4-dimethyl-1-hexene.
[0058] According to one embodiment of the present invention, the content of the olefin polymer block relative to the total content of the block copolymer can be about 40 wt % to about 90 wt %, about 60 wt % to about 85 wt %, or about 65 wt % to about 80 wt %, and within this range, there is an effect of excellent mechanical properties and processability of the block copolymer.
[0059] According to one embodiment of the present invention, if the olefin polymer block contains ethylene monomer units, the content of the ethylene monomer units relative to the total content of the block copolymer can be about 20 wt % to about 70 wt %, about 30 wt % to about 60 wt %, or about 35 wt % to about 50 wt %, and within this range, there is an effect of excellent mechanical properties and processability of the block copolymer.
[0060] According to one embodiment of the present invention, if the olefin polymer block contains α-olefin monomer units, the content of the α-olefin monomer units relative to the total content of the block copolymer can be about 10 wt % to about 50 wt %, about 15 wt % to about 45 wt %, or about 20 wt % to about 40 wt %, and within this range, there is an effect of excellent mechanical properties and processability of the block copolymer.
[0061] According to one embodiment of the present invention, resin combination can include the polyolefin resin of the amount of about 40 weight % to about 80 weight % and the block copolymer of the amount of about 20 weight % to about 60 weight %.As a specific example, resin combination can include about 40 weight %, about 41 weight %, about 42 weight %, about 43 weight %, about 44 weight %, about 45 weight %, about 46 weight %, about 47 weight %, about 48 weight %, about 49 weight %, or about 50 weight %, and also about 80 weight %, about 79 weight %, about 78 weight %, about 77 weight %, about 76 weight %, about 75 weight %, about 74 weight %, about 73 weight %, about 72 weight %, about 71 weight %, or about 70 weight % polyolefin resin.
[0062] According to one embodiment of the present invention, the resin composition may include a polyolefin resin and a block copolymer in a weight ratio of about 1:0.11 to about 1:9, and as a specific example, may include a polyolefin resin and a block copolymer in a weight ratio of about 1:0.11-about 4, about 1:0.11-about 3, about 1:0.11-about 2.4, about 1:0.11-about 1.5, about 1:0.11-about 1, about 1:0.17-about 1.5, about 1:0.17-about 1.5, or about 1:0.17-about 0.25.
[0063] According to one embodiment of the present invention, when the resin composition includes the polyolefin resin and the block copolymer within the above range, the impact strength of the resin composition can be further improved, and the fluidity can be prevented from decreasing, thereby improving the processability.
[0064] According to one embodiment of the present invention, the resin composition may further selectively include an inorganic filler to improve the mechanical properties of the resin composition. The inorganic filler may specifically be a powder filler, a flaky filler, a fiber filler or a spherical filler, or any one thereof or a mixture of two or more thereof may be used. As a specific example, the powder filler may be: natural silicic acid or silicate, such as fine powder talc, kaolinite, calcined clay or sericite; carbonate, such as precipitated calcium carbonate, heavy calcium carbonate or magnesium carbonate; hydroxide, such as aluminum hydroxide or magnesium hydroxide; oxide, such as zinc oxide, magnesium oxide or titanium oxide; synthetic silicic acid or silicate, such as hydrated calcium silicate, hydrated aluminum silicate, hydrated silicic acid or silicic anhydride; and silicon carbide, etc. In addition, the flaky filler may be mica, etc. In addition, the fiber filler may be basic magnesium sulfate whisker, calcium titanate whisker, aluminum borate whisker, sepiolite, processed mineral fiber (PMF), potassium titanate, etc. In addition, the spherical filler may be glass balls, etc. Among them, the inorganic filler may be talc.
[0065] According to one embodiment of the present invention, the inorganic filler can be surface treated to improve the strength performance and molding processability of the resin composition. Specifically, the inorganic filler can be physically or chemically surface treated using a surface treatment agent such as a silane coupling agent, a higher fatty acid, a fatty acid metal salt, an unsaturated organic acid, an organic titanate, a resin acid or polyethylene glycol.
[0066] According to one embodiment of the present invention, the average particle size (D 50 ) may be about 1 μm to about 20 μm, specifically about 3 μm to about 15 μm, more specifically about 5 μm to about 10 μm, and within this range, the resin composition may be uniformly dispersed, so that mechanical properties may be further improved. The average particle size (D 50 ) can be defined as the particle size at which the volume cumulative particle size distribution is 50%. In the present invention, the average particle size (D 50 ) can be measured by, for example, electron microscope observation using a scanning electron microscope (SEM), a field emission scanning electron microscope (FE-SEM), or the like, or by a laser diffraction method. More specifically, when measured by the laser diffraction method, the inorganic filler particles may be dispersed in a dispersion medium, which is then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) to measure the average particle size (D ) at 50% of the volume cumulative particle size distribution. 50 ).
[0067] According to one embodiment of the present invention, the content of the inorganic filler can be about 0.1 parts by weight to about 40 parts by weight, or about 0.1 parts by weight to about 20 parts by weight, relative to 100 parts by weight of the total content of the polyolefin resin and the block copolymer, and within this range, deterioration of processability can be prevented and mechanical properties can be further improved.
[0068] According to one embodiment of the present invention, a resin composition can be prepared by adding a polyolefin resin and an optional inorganic filler to a block copolymer, then mixing, and then heat treating the mixture. The mixing process can be performed according to a typical method. Specifically, a super mixer or a ribbon mixer can be used to perform mixing.
[0069] According to one embodiment of the present invention, during the mixing process, if necessary, additives such as antioxidants, heat stabilizers, UV stabilizers, antistatic agents, etc. may also be included, and in order to improve the paintability, additives with a small amount of adhesive resin or polar groups may be further selectively used within an appropriate content range.
[0070] According to one embodiment of the present invention, the heat treatment may be performed at a temperature equal to or higher than the melting point of the polyolefin resin, for example, equal to or lower than 210° C. The heat treatment process may be performed using various blending processing devices such as a twin-screw extruder, a single-screw extruder, a roll mill, a kneader, or a Banbury mixer.
[0071] According to one embodiment of the present invention, the resin composition can be used for hollow molding, extrusion molding or injection molding for packaging, construction, household products, etc. in various fields and applications, such as materials for automobiles, wires, toys, textiles or medical products. In particular, the thermoplastic resin composition has excellent toughness and impact strength at low temperatures and room temperatures, and also has excellent physical properties such as heat resistance and rigidity, and can therefore be effectively used for interior and exterior parts of automobiles.
[0072] The present invention provides a method for preparing a resin composition, which may be the method for preparing the above-mentioned resin composition.
[0073] According to one embodiment of the present invention, the method for preparing a resin composition may include: (S10): in the presence of a chain transfer agent, polymerizing one or more olefin monomers by using a transition metal catalyst to prepare an olefin polymer block intermediate; (S20): in the presence of the olefin polymer block intermediate prepared in step S10, introducing an initiator and an aromatic vinyl monomer and polymerizing them to prepare a block copolymer; and (S30): blending the block copolymer prepared in step (S20) with a polyolefin resin.
[0074] According to one embodiment of the present invention, step S10 is a step of preparing an olefin polymer block intermediate by polymerizing one or more olefin monomers using a transition metal catalyst in the presence of a chain transfer agent.
[0075] According to one embodiment of the present invention, the transition metal catalyst is a catalyst for growing an olefin-based polymer by coordination chain transfer polymerization, and may be a catalyst composition including a transition metal catalyst as a main catalyst, a co-catalyst, and trialkylaluminum.
[0076] According to one embodiment of the present invention, the transition metal catalyst may be a transition metal catalyst represented by Formula 1 below.
[0077] [Formula 1]
[0078]
[0079] In the above formula 1, M is Ti, Zr or Hf, R1 to R4 are each independently hydrogen, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, or substituted or unsubstituted C6-C20 aryl, wherein two or more adjacent groups thereof may be connected to each other and form a ring, R5 and R6 are each independently hydrogen, substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, or substituted or unsubstituted C6-C20 aryl, wherein the substitution is performed by C1-C12 alkyl, R7 are each independently substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C4-C20 cycloalkyl, or a substituted or unsubstituted C6-C20 aryl group, n is 1 to 5, and Y1 and Y2 are each independently a halogen group, a C1-C20 alkyl group, a C2 to C20 alkenyl group, a C2 to C20 alkynyl group, a C3-C20 cycloalkyl group, a C6-C20 aryl group, a C7-C20 alkaryl group, a C7-C20 aralkyl group, a C5-C20 heteroaryl group, a C1-C20 alkoxy group, a substituted or unsubstituted C5-C20 aryloxy group, a C1-C20 alkylamino group, a C5-C20 arylamine group, a C1-C20 alkylthio group, a C5-C20 arylthio group, a C1-C20 alkylsilyl group, a C5-C20 arylsilyl group, a hydroxyl group, an amino group, a thiol group, a silyl group, a cyano group or a nitro group.
[0080] According to one embodiment of the present invention, in the above formula 1, M may be Hf, and R1 to R4 may be each independently hydrogen, or a substituted or unsubstituted C1-C20 alkyl group, wherein two or more adjacent groups thereof may be connected to each other and form a ring. Alternatively, R1 and R2 may each independently be a C1-C20 alkyl group, which are connected to each other and form a C5-C20 aromatic ring, and R3 and R4 may be hydrogen.
[0081] According to one embodiment of the present invention, in the above formula 1, R5 and R6 may each independently be hydrogen, or a substituted or unsubstituted C6-C20 aryl group, wherein the substitution may be a C1-C6 alkyl substitution.
[0082] According to one embodiment of the present invention, in the above Formula 1, R7 may be each independently a substituted or unsubstituted C4-C20 alkyl group, a substituted or unsubstituted C4-C20 cycloalkyl group, or a substituted or unsubstituted C6-C20 aryl group.
[0083] According to one embodiment of the present invention, in the above Formula 1, n may be 1 to 3, preferably 2, and X1 and X2 may each independently be a C1-C20 alkyl group.
[0084] According to one embodiment of the present invention, the transition metal compound represented by the above formula 1 may be a compound represented by the following formula 1a.
[0085] [Formula 1a]
[0086]
[0087] In the above Formula 1a, M, R5 to R7, and Y1 and Y2 are the same as defined above.
[0088] According to one embodiment of the present invention, the transition metal compound represented by the above formula 1 can be selected from the following compounds, but is not limited thereto. All transition metal compounds corresponding to formula 1 are included in the present invention.
[0089] [Formula 1-1]
[0090]
[0091] [Formula 1-2]
[0092]
[0093] [Formula 1-3]
[0094]
[0095] [Formula 1-4]
[0096]
[0097] [Formula 1-5]
[0098]
[0099] [Formula 1-6]
[0100]
[0101] [Formula 1-7]
[0102]
[0103] [Formula 1-8]
[0104]
[0105] According to one embodiment of the present disclosure, the transition metal compound represented by the above Formula 1 may be prepared using a ligand compound represented by the following Formula 2.
[0106] [Formula 2]
[0107]
[0108] In the above formula 2, R1 to R4 are each independently a substituted or unsubstituted C1-C20 alkyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, or a substituted or unsubstituted C6-C20 aryl group, wherein two or more adjacent groups thereof may be connected to each other and form a ring, R5 and R6 are each independently hydrogen, a substituted or unsubstituted C1-C20 alkyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, or a substituted or unsubstituted C6-C20 aryl group, wherein the substitution is performed by a C1-C12 alkyl group, R7 are each independently a substituted or unsubstituted C4-C20 alkyl group, a substituted or unsubstituted C4-C20 cycloalkyl group, or a substituted or unsubstituted C6-C20 aryl group, and n is 1 to 5.
[0109] According to one embodiment of the present invention, the transition metal compound represented by the above formula 1 can be prepared by reacting a ligand compound represented by the following formula 2 with a compound represented by the following formula 3.
[0110] [Formula 2]
[0111]
[0112] [Formula 3]
[0113] M(Y1Y2)2
[0114] In the above formula,
[0115] R1 to R7, M, Y1 and Y2 are the same as described above.
[0116] According to one embodiment of the present invention, when preparing the transition metal compound represented by the following formula 1, the reaction may be carried out through the following process.
[0117] [Reaction Scheme 1]
[0118]
[0119] [Reaction Scheme 2]
[0120]
[0121] According to one embodiment of the present invention, the organic zinc compound is a material used as a chain transfer agent to induce chain transfer during the preparation of the polymerization reaction, thereby preparing a copolymer, wherein the chain transfer agent may be a chain transfer agent for preparing a block copolymer by coordination chain transfer polymerization.
[0122] According to one embodiment of the present invention, the chain transfer agent may include an organic zinc compound represented by Formula 5 below, specifically, the chain transfer agent may include 96 mol% or more of the organic zinc compound represented by Formula 5 below, and preferably, the chain transfer agent may not include any side reaction products except the organic zinc compound represented by Formula 5 below.
[0123] [Formula 5]
[0124]
[0125] In the above formula 5, R8 and R 10 can be independently a single bond or a C1-C10 alkylene group, R9 can be a C1-C10 alkylene group or -SiR 11 R 12 -, and R 11 and R 12 Each may independently be a C1-C10 alkyl group.
[0126] According to one embodiment of the present invention, in the above formula 5, R8 and R 10 can be independently a single bond or a C1-C10 alkylene group, R9 can be a C1-C10 alkylene group or -SiR 11 R 12 -, and R 11 and R 12 Each may independently be a C1-C10 alkyl group.
[0127] According to one embodiment of the present invention, the organic zinc compound represented by Formula 5 may be one selected from the group consisting of organic zinc compounds represented by Formulas 5-1 to 5-4, preferably any one of Formulas 5-3 and 5-4.
[0128] [Formula 5-1]
[0129]
[0130] [Formula 5-2]
[0131]
[0132] [Formula 5-3]
[0133]
[0134] [Formula 5-4]
[0135]
[0136] According to one embodiment of the present invention, the chain transfer agent may contain 97 mol% or more of the organic zinc compound of the above-mentioned formula 5, more preferably 98 mol% or more, or 99 mol% or more, and most preferably may not contain any side reaction products other than the organic zinc compound. This means that in addition to the organic zinc compound represented by formula 5, the chain transfer agent does not contain any side reaction products (such as dimers) and impurities containing chlorine or magnesium. That is, the chain transfer agent may only contain the organic zinc compound represented by the above-mentioned formula 5.
[0137] According to one embodiment of the present invention, when one or more olefin monomers, as a specific example, ethylene and α-olefin monomers are reacted in the presence of a catalyst composition comprising a transition metal compound and using an organic zinc compound represented by the above formula 5 as a chain transfer agent, ethylene and α-olefin monomers are inserted into the zinc (Zn) of the organic zinc compound and R 10 between them, so that aggregation can be performed.
[0138] According to one embodiment of the present invention, when an olefin polymer block is prepared by reacting ethylene and an α-olefin monomer using the compound of Formula 5 as an organic zinc compound, an olefin polymer block intermediate is prepared, and the olefin polymer block intermediate can be represented by Formula 6 below.
[0139] [Formula 6]
[0140]
[0141] In the above formula 6, R8 and R 10 can be independently a single bond or a C1-C10 alkylene group, R9 can be a C1-C10 alkylene group or -SiR 11 R 12 -, R 11 and R 12 Each may independently be a C1-C10 alkyl group, and PO may be an olefin polymer block.
[0142] According to one embodiment of the present invention, the organic zinc compound can be prepared by a preparation method comprising the following steps: preparing a Grignard reagent containing a styrene portion, and reacting the prepared Grignard reagent with a zinc compound to prepare the organic zinc compound shown in Formula 5 above, and the organic zinc compound can be an alkyl zinc alkoxide.
[0143] According to one embodiment of the present invention, the organozinc compound shown in the above formula 5 prepared according to the preparation method of the organozinc compound is synthesized as a single compound, and therefore does not contain any side reaction products (e.g., dimers), and further, does not contain chlorine-containing impurities that may become catalytic poisons, such as organic zinc chloride (R-Zn-Cl). In addition, when the organozinc compound shown in the above formula 5 is prepared according to the preparation method of the organozinc compound, the organozinc compound is synthesized as a single compound, and thus the synthesis reproducibility is excellent. At the same time, when preparing the organozinc compound, in order not to contain side reaction products and impurities as in the present invention, it may be important to select a Grignard reagent containing a styrene moiety and a zinc compound.
[0144] According to one embodiment of the present invention, the Grignard reagent containing a styrene moiety may be represented by Formula 7 below.
[0145] [Formula 7]
[0146]
[0147] In the above formula 7, R8 and R 10 can be independently a single bond or a C1-C10 alkylene group, R9 can be a C1-C10 alkylene group or -SiR 11 R 12 -, R 11 and R 12 may each independently be a C1-C10 alkyl group, and X may be a halogen group.
[0148] In addition, according to one embodiment of the present invention, in the above formula 7, R8 and R 10 can be independently a single bond or a C1-C10 alkylene group, R9 can be a C1-C10 alkylene group or -SiR 11 R 12 -, and R 11 and R 12 Each may independently be a C1-C10 alkyl group.
[0149] According to one embodiment of the present invention, the Grignard reagent containing a styrene moiety and represented by Formula 7 may be one selected from the group consisting of respective Grignard reagents containing a styrene moiety represented by the following Formulae 7-1 to 7-4.
[0150] [Formula 7-1]
[0151]
[0152] [Formula 7-2]
[0153]
[0154] [Formula 7-3]
[0155]
[0156] [Formula 7-4]
[0157]
[0158] According to one embodiment of the present invention, the Grignard reagent including a styrene moiety and represented by the above Formula 7 may be prepared by a reaction between a halide and magnesium, wherein the halide (X) replaces R8, and magnesium is specifically magnesium powder or magnesium metal.
[0159] According to one embodiment of the present invention, the Grignard reagent containing a styrene moiety and represented by the above Formula 7 may be prepared by a reaction between a compound represented by the following Formula 8 and magnesium (specifically, magnesium powder or magnesium metal).
[0160] [Formula 8]
[0161]
[0162] In the above formula 8, R8 and R 10 can be independently a single bond or a C1-C10 alkylene group, R9 can be a C1-C10 alkylene group or -SiR 11 R 12 -, R 11 and R 12 may each independently be a C1-C10 alkyl group, and X may be a halogen group.
[0163] According to one embodiment of the present invention, in the above formula 8, R8 and R 10 can be independently a single bond or a C1-C3 alkylene group, R9 can be a C1-C3 alkylene group or -SiR 11 R 12 -, R 11 and R 12 may each independently be a C1-C3 alkyl group, and X may be a halogen group.
[0164] According to one embodiment of the present invention, in the above formula 8, R8 and R 10 can be independently a single bond or a C1 alkylene group, R9 can be a C1 alkylene group or -SiR 11 R 12 -, R 11 and R 12 may each independently be a C1 alkyl group, and X may be a halogen group selected from the group consisting of Cl, Br and I.
[0165] According to one embodiment of the present invention, the compound represented by the above formula 8 may be one selected from the group consisting of compounds represented by the following formulae 8-1 to 8-4.
[0166] [Formula 8-1]
[0167]
[0168] [Formula 8-2]
[0169]
[0170] [Formula 8-3]
[0171]
[0172] [Formula 8-4]
[0173]
[0174] According to one embodiment of the present invention, when preparing a Grignard reagent containing a styrene portion and represented by the above formula 7, the reaction between the compound represented by the above formula 8 and magnesium powder or magnesium metal can be carried out as follows: in terms of mole percentage, the mole percentage of magnesium powder or magnesium metal is excessive relative to 1 mole of the compound represented by the above formula 8, that is, the mole percentage is greater than 1 mole, and in this case, about 50 mol% or more, about 60 mol% or more, about 70 mol% or more, about 80 mol% or more, about 90 mol% or more, about 95 mol% or more, or about 99 mol% or more of the compound represented by formula 8 can be converted into a Grignard reagent containing a styrene portion.
[0175] According to one embodiment of the present invention, the reaction between the compound represented by the above formula 8 and magnesium powder or magnesium metal can be carried out at a molar ratio of greater than 1:1 to 10, greater than 1:1 to 5, greater than 1:1 to 2 or 1:1.01 to 1.60, and within this range, the conversion rate of the Grignard reagent containing a styrene portion and represented by formula 7 is high, and the content of residual magnesium after the reaction is minimized to facilitate the removal of residual magnesium powder or magnesium metal.
[0176] According to one embodiment of the present invention, when preparing an organic zinc compound, the zinc compound needs to be a zinc-based zinc compound capable of inducing zinc substitution of two organic groups of the same type. Therefore, zinc chloride (ZnCl2) can be easily considered, but when zinc chloride is used as the zinc compound, there is a problem that impurities containing chlorine (e.g., alkyl zinc chloride) as a catalyst poison may remain. Therefore, in the present invention, an alkyl zinc alkoxide is used as the zinc compound.
[0177] According to one embodiment of the present invention, the alkyl group of the alkyl zinc alkoxide may be a C1-C10 alkyl group, a C1-C5 alkyl group, a C1-C3 alkyl group or an ethyl group, and the alkoxide group may be a C1-C10 alkoxide group, a C1-C5 alkoxide group, a C1-C3 alkoxide group or a methoxide group. As a specific example, the zinc compound may be ethyl zinc methoxide.
[0178] According to one embodiment of the present invention, alkyl zinc alkoxide can be prepared from dialkyl zinc. As a specific example, alkyl zinc alkoxide can be prepared by reacting dialkyl zinc with alcohol in situ. At this time, the alkyl group of the dialkyl zinc can be the same as the alkyl group of the above-mentioned alkyl zinc alkoxide, and the alcohol can be an alcohol in which hydrogen is bonded to the alkoxide group of the above-mentioned alkyl zinc alkoxide.
[0179] According to one embodiment of the present invention, when an alkyl zinc alkoxide is used as the zinc compound, during the reaction of the Grignard reagent with the zinc compound, a magnesium halide alkoxide is generated, which is an insoluble salt that is easily filtered, thereby preventing impurities from remaining.
[0180] According to one embodiment of the present invention, based on the molar ratio, the reaction between the Grignard reagent and the zinc compound can be carried out at a molar ratio of 10:1 to 1:10, 5:1 to 1:5, 3:1 to 1:3, 2:1 to 1:2, 1.5:1 to 1:1.5, or 1:1. Within this range, the organozinc compound is synthesized as a single compound and therefore does not contain any side reaction products (such as dimers) and does not contain chlorine-containing impurities that may act as catalyst poisons, which has the effect of easily removing magnesium-containing impurities that may act as catalyst poisons.
[0181] According to one embodiment of the present invention, all steps and all reactions of the method for preparing the zinc compound can be carried out in an organic solvent, and the reaction temperature and reaction pressure can be adjusted for the purpose of increasing the yield and purity.
[0182] In one embodiment of the present invention, the method for preparing the zinc compound replaces the borane compound containing the typical styrene moiety with the Grignard reagent containing the styrene moiety, and replaces the alkyl zinc or zinc chloride with the alkyl zinc alkoxide, thereby completely removing the catalytic poison.
[0183] According to one embodiment of the present invention, the catalyst composition may include an aluminoxane compound and a trialkylaluminum. As a specific example, the catalyst composition may include an aluminoxane compound and a trialkylaluminum represented by the following formula 9. As described above, if the catalyst composition includes an aluminoxane compound and a trialkylaluminum, when a resin composition is prepared from a block copolymer prepared therefrom, the particle size and dispersion of the block copolymer can be controlled to control the size of the domain and the distance between multiple domains.
[0184] According to one embodiment of the present invention, the aluminoxane compound represented by the following Formula 9 may be used as a co-catalyst, a scavenger, or a co-catalyst and a scavenger.
[0185] [Formula 9]
[0186] -[Al(R a )-O] m -
[0187] In the above formula 9, R a Each is independently a halogen radical, a C1-C20 hydrocarbon radical, or a halogen-substituted C1-C20 hydrocarbon radical, and m is an integer of 2 or greater.
[0188] According to one embodiment of the present invention, the compound shown in the above formula 9 is not particularly limited as long as it is an alkylaluminoxane. Preferred examples include modified methylaluminoxane (MMAO), methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane, butylaluminoxane, etc., and a particularly preferred compound may be modified methylaluminoxane (MMAO).
[0189] According to one embodiment of the present invention, the compound shown in the above formula 9 is a compound in the form of an oligomer generated by the reaction of alkyl aluminum and water, and when the compound is used as a co-catalyst, chain transfer is reduced. Therefore, a high molecular weight copolymer can be prepared, and homopolymerization olefins as a side reaction can also be prevented from being produced. Therefore, ultimately, a block copolymer showing excellent physical properties such as high tensile strength can be prepared.
[0190] According to one embodiment of the present invention, trialkylaluminum can be used as an additive, and the additive is used to control the structure of the block copolymer by inducing the alkyl exchange with the olefin polymer block intermediate when polymerizing the block copolymer. As a specific example, the trialkylaluminum can be a trialkylaluminum comprising a C1-C12 alkyl, and as a specific example, it can be a trialkylaluminum comprising a C3-C12, C6-C12, C6-C10 or C6-C8 alkyl. As a more specific example, the trialkylaluminum can be selected from one or more of the group consisting of trimethylaluminum, triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, tri-n-pentylaluminum, trihexylaluminum, trioctylaluminum and tridecylaluminum, and as a more specific example, it can be trioctylaluminum.
[0191] According to one embodiment of the present invention, the catalyst composition may include an aluminoxane compound and a trialkyl aluminum in a molar ratio of 1:0.01 to 10.0. As a specific example, the catalyst composition may include an aluminoxane compound and a trialkyl aluminum in a molar ratio of 1:0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may also include 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, 4.0 or less, 3.0 or less, 2.0 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, or 0.6 or less, and within this range, it is easy to control the size of the domain of the resin composition and the distance between multiple domains.
[0192] According to one embodiment of the present invention, when a transition metal compound represented by Formula 1, an aluminoxane-based compound represented by Formula 9, and trialkylaluminum are combined and used as a catalyst composition, a block copolymer satisfying the above conditions may be manufactured.
[0193] According to one embodiment of the present invention, the catalyst composition may be used in the form of a transition metal compound represented by Formula 1, an aluminoxane compound represented by Formula 9, and trialkylaluminum supported on a carrier. As the carrier, silica or alumina may be used, but the carrier is not limited thereto.
[0194] According to one embodiment of the present invention, the catalyst compound includes a compound represented by Formula 10 below.
[0195] [Formula 10]
[0196] [LH] + [Z(A)4] - or [L] + [Z(A)4] -
[0197] In the above formula 10, Z is a Group 13 element, A is each independently a C6-C20 aryl group in which one or more hydrogen atoms may be substituted by a substituent, or a C1-C20 alkyl group, and the substituent of A is a halogen, a C1-C20 hydrocarbon group, a C1-C20 alkoxy group or a C6-C20 aryloxy group.
[0198] According to one embodiment of the present invention, step S10 can be performed in a uniform solution state. At this time, as a solvent, a hydrocarbon solvent or an olefin monomer itself can be used as a medium. Examples of hydrocarbon solvents can be C4-C20 aliphatic hydrocarbon solvents, particularly isobutane, hexane, cyclohexane, methylcyclohexane, etc. The solvent can be used separately or in combination of two or more.
[0199] According to one embodiment of the present invention, the polymerization temperature of step S10 may be changed according to the reaction materials, reaction conditions, etc., but may be specifically about 70° C. to about 170° C., specifically about 80° C. to about 150° C., or about 90° C. to about 120° C. Within the above range, the solubility of the polymer may be increased and the catalyst may be thermally stabilized.
[0200] According to one embodiment of the present invention, the polymerization in step S10 may be carried out in a batch, semi-continuous or continuous manner, or may be carried out in two or more steps with different reaction conditions.
[0201] According to one embodiment of the present invention, the olefin polymer block intermediate prepared in step S10 can be used as a precursor for preparing the block copolymer of the present invention through a polymerization reaction in step S20 as described below.
[0202] According to one embodiment of the present invention, the olefin-based monomer may be ethylene and an α-olefin-based monomer, and the α-olefin-based monomer is the same as that of the previously described resin composition.
[0203] According to one embodiment of the present invention, step S20 is for preparing a block copolymer by reacting an aromatic vinyl-based monomer with an olefin-based polymer block intermediate in the presence of a polymerization initiator.
[0204] According to one embodiment of the present invention, in step S20, aromatic vinyl monomers can be continuously inserted between zinc-carbon bonds of (polyolefinyl)2Zn contained in the olefin polymer block intermediate formed in step S10 to form aromatic vinyl polymer block chains, and at the same time, the styrene groups derived from the chain extender present at the ends of the compound prepared in step S10 participate as copolymerization sites with the aromatic vinyl monomers to thereby connect to the aromatic vinyl polymer block chains. In addition, the block copolymer prepared by the above process can be easily quenched by reaction of the end groups with water, oxygen or organic acid, thereby converting the block copolymer into an industrially useful polyolefin-polystyrene multi-block copolymer.
[0205] According to one embodiment of the present invention, the aromatic vinyl-based monomer is the same as that in the previously described resin composition.
[0206] According to one embodiment of the present invention, the polymerization initiator may be an anionic polymerization initiator, and as a specific example, may be an alkyl lithium compound represented by the following Formula 11.
[0207] [Formula 11]
[0208]
[0209] In the above formula 11, R 13 is hydrogen or a C1-C20 hydrocarbon group, and Am is an amine compound represented by the following formula 12, and
[0210] [Formula 12]
[0211]
[0212] In the above formula 12, R 14 To R 18 Each is independently hydrogen or a C1-C20 hydrocarbon group, and a and b are each independently an integer from 0 to 3, wherein a and b are not 0 at the same time.
[0213] According to one embodiment of the present invention, R 13 It can be hydrogen, C1-C20 alkyl, C3-C20 cycloalkyl, or substituted or unsubstituted C7-C20 aralkyl. 14 To R 18 They may each independently be hydrogen, a C1-C20 alkyl group, a C1-C20 alkenyl group, a C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C7-C20 aralkyl group, and a and b may each independently be an integer from 0 to 2.
[0214] According to one embodiment of the present invention, R 13 To R 18 may each independently be hydrogen or a C1-C20 alkyl group, wherein a may be 1 or 2, and b may be 0 or 1. Specifically, a may be an integer from 1 to 3, b may be an integer from 0 to 3, more specifically, a may be 1 or 2, b may be an integer from 0 to 2, even more specifically, a may be 1 or 2, and b may be 0 or 1.
[0215] According to one embodiment of the present invention, in the above formula 11, the Am can be specifically represented by the following formula 13 or formula 14.
[0216] [Formula 13]
[0217]
[0218] [Formula 14]
[0219]
[0220] In the above formula, R 14 , R 15 , and R 18 Each is independently hydrogen or C1-C20 alkyl.
[0221] According to one embodiment of the present invention, in the above formula 11, the Am can be specifically represented by the following formula 13a or formula 14a.
[0222] [Formula 13]
[0223]
[0224] [Formula 14a]
[0225]
[0226] According to one embodiment of the present invention, the polymerization initiator represented by Formula 11 can be prepared by the following preparation method. The preparation method of the polymerization initiator includes introducing a compound represented by Formula 16 and a compound represented by Formula 12 to react in the presence of a compound represented by Formula 15.
[0227] [Formula 12]
[0228]
[0229] [Formula 15]
[0230] B-Li
[0231] [Formula 16]
[0232]
[0233] In the above formula, R 13 To R 18 are each independently hydrogen or a C1-C20 hydrocarbon group, a and b are each independently an integer from 0 to 3, wherein a and b are not 0 at the same time, and B is a C1-C20 alkyl group.
[0234] According to one embodiment of the present invention, R 13 It can be hydrogen or C1-C20 hydrocarbon group, R 14 To R 18 They may each independently be hydrogen, a C1-C20 alkyl, a C1-C20 alkenyl, a C3-C20 cycloalkyl, a substituted or unsubstituted C6-C20 aryl, or a substituted or unsubstituted C7-C20 arylalkyl, a and b may each independently be an integer from 0 to 2, and B may be a C1-C12 alkyl.
[0235] According to one embodiment of the present invention, R 14 To R 18may be each independently hydrogen or a C1-C20 alkyl group, a may be an integer of 1 or 2, b may be an integer of 0 or 1, and B may be a C1-C8 alkyl group. Specifically, a may be an integer of 1 to 3, b may be an integer of 0 to 3, more specifically, a may be 1 or 2, b may be an integer of 0 to 2, even more specifically, a may be 1 or 2, and b may be 0 or 1.
[0236] According to one embodiment of the present invention, the alkyl lithium compound represented by Formula 16 may be, for example, n-BuLi, which is a material widely used as an initiator for anionic polymerization, is easily available, and has excellent unit cost efficiency.
[0237] According to one embodiment of the present invention, in the method for preparing a polymerization initiator, the reaction process of the compound represented by the above formula 16 and the compound represented by the above formula 15 can be carried out first, and then the compound represented by the above formula 12 can be reacted therewith to prepare the compound represented by the above formula 11. Specifically, the compound represented by the above formula 16 reacts with the compound represented by the above formula 15 to obtain allyl lithium as an intermediate, and the allyl lithium reacts with the compound represented by the formula 12 to finally form the polymerization initiator represented by the above formula 11.
[0238] According to one embodiment of the present invention, the process of reacting the compound represented by Formula 16 and the compound represented by Formula 12 in the presence of the compound represented by Formula 15 can be carried out without an additional solvent. The condition without an additional solvent means that in the presence of the compound represented by Formula 16, there is no additional compound that can be used as a solvent except the compound represented by Formula 15 and the compound represented by Formula 12, or that a trace amount of an additional solvent exists, so it does not react significantly with the compound represented by Formula 15. When the reaction is carried out without an additional solvent, the reaction of the compound represented by Formula 15 with the compound represented by Formula 16 is the main reaction, so that the polymerization initiator represented by Formula 11 can be effectively prepared. When an additional solvent is present, the polymerization initiator of Formula 11, the compound produced by reacting the compound represented by Formula 15 with the compound represented by Formula 12, and the compound produced by the decomposition of the compound represented by Formula 15 with the compound represented by Formula 12 are all mixed and present, so it is not effective.
[0239] According to one embodiment of the present invention, the polymerization initiator may be a silyl compound represented by Formula 17 below.
[0240] [Formula 17]
[0241]
[0242] In the above formula 17, R19 To R 21 may be each independently hydrogen or a C1-C20 hydrocarbon group, and R 22 It can be a C1-C20 divalent alkylene group. As a specific example, R 19 To R 21 may be each independently a C1-C10 hydrocarbon group, and R 22 It may be a C1-C10 divalent alkylene group. As a more specific example, R 19 To R 21 can be each independently a C1-C6 hydrocarbon group, and R 22 It can be a C1-C6 divalent alkylene group. In the above formula 17, Li can be located at R 22 The carbon at the terminal of the alkylene group is ionically bonded, and therefore, the silyl compound represented by the above formula 17 can be used as an anionic polymerization initiator.
[0243] According to one embodiment of the present invention, the silyl compound represented by Formula 17 may be (trimethylsilyl)methyllithium. In addition, the silyl compound may be mixed with the amine compound represented by Formula 12 and used in the form of a complex.
[0244] According to one embodiment of the present invention, in step S20, a polymerization initiator is used as an initiator so that a polystyrene-based chain can grow from the organic zinc compound prepared in step S10, particularly a polyolefin of (polyolefinyl)2-zinc ((polyolefinyl)2Zn), wherein the olefin-based polymer chain has grown around zinc (Zn) as the center.
[0245] According to one embodiment of the present invention, step S30 is a step of blending the block copolymer prepared in step S20 with a polyolefin resin. Here, the blending of the block copolymer and the polyolefin resin is the same as that described above for the resin composition.
[0246] Hereinafter, the embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments set forth herein.
[0247] Reagents and experimental conditions
[0248] All experiments were performed using a standard glove box and Schlenk technique under an inert atmosphere. Toluene, hexane, and tetrahydrofuran (THF) were distilled from benzophenone and used. Methylcyclohexane (anhydrous grade) used in the polymerization reaction was purchased from Tokyo Chemical Industry (TCI) and purified with Na / K alloy and used. Sublimation grade HfCl4 was purchased from Streme and used as is.
[0249] Recorded using ECZ 600 instrument (JEOL) 1 H NMR (600 MHz) and 13 C NMR (150 MHz) spectrum.
[0250] GPC data were analyzed in 1,2-4-trichlorobenzene at 160°C using a PL-GPC 220 system equipped with a refractive index detector and two columns (PLarian Mixed-B 7.5 x 300 mm Varian [Polymer Lab]).
[0251] (1) Production of the transition metal compound represented by formula 1-1
[0252] [Formula 1-1]
[0253]
[0254] 1) Preparation of ligand compounds
[0255] [Solution 1]
[0256]
[0257] 2,6-Dicyclohexylaniline (0.772 g, 3.00 mmol) and 6-bromo-2-pyridinecarboxaldehyde (0.558 g, 3.00 mmol) were dissolved in toluene (5 mL) and molecular sieves were added. The mixture was heated to 70 ° C overnight with stirring. After filtration, the solvent was removed from a rotary evaporator. A yellow solid (1.07 g, 84%) was obtained.
[0258] 1H NMR (C6D6): δ8.41(s,1H,NCH),8.09(d,J=7.8Hz,1H),7.53(m,3H),6.85(d,J=7.8Hz,1H),6.63(t,J=7.8Hz,1H),2.74(m, 2H), 1.87 (d, J = 12Hz, 4H), 1.64 (d, J = 12.6Hz, 4H), 1.54 (d, J = 10.8Hz, 2H), 1.39 (quartet, J = 10.2Hz, 4H), 1.11 (m, 6H) ppm.
[0259] 13 C NMR (C6D6): δ26.55,27.33,34.25,39.30,119.42,124.32,125.21,129.83,136.68,138.82,142.54,148.94,155.95,162.06ppm.
[0260] HRMS(EI): m / z calculated ([M + ]C 24 H 29 BrN2) 424.1514. Measured value: 424.1516
[0261] Under nitrogen, compound (1.07g, 2.51mmol), 1-naphthaleneboric acid (0.453g, 2.64mmol), Na2CO3 (0.700g, 6.60mmol) and toluene (5mL) were charged into a Schlenk flask. A solution of (Ph3P)4Pd (7.83mg, 0.00678mmol) was added to degassed H2O / EtOH (1mL, v / v, 1:1) and toluene (1mL). A light yellow oil was obtained on silica gel by column chromatography using ethyl acetate (v / v, 90:3:1) containing hexane and a small amount of triethylamine (0.712g, 60%).
[0262] 1 H NMR (C6D6): δ8.70(s,1H,NCH),8.41(d,J=7.8Hz,1H),8.31(d,J=7.8Hz,1H),7.68(d,J=7.2Hz,1H),7.65(d,J=7.8Hz,1H),7.54(d,J=7.2Hz,1H ),7.27(m,4H),7.20(m,4H),2.93(m,2H),1.90(d,J=12Hz,4H),1.61(d,J=13.2Hz,4H),1.50(d,J=12.6Hz,2H),1.38(m,4H),1.11(m,6H),ppm.
[0263] 13 C NMR(C6D6): δ26.63,27.38,34.35,39.36,119.21,124.32,124.98,125.50,126.15,126.21,126.64,126.7 5,128.15,128.73,129.38,131.81,134.52,136.94,137.14,138.52,149.48,155.13,159.79,164.05ppm.
[0264] HRMS(EI): m / z calculated ([M + ]C 34 H 36 N2)472.2878. Measured value: 472.2878
[0265] 2-Isopropylphenyl lithium (0.114 g, 0.904 mmol) dissolved in ether (8 mL) was added dropwise to a Schlenk flask containing a solution of the compound (0.247 g, 0.523 mmol) in ether (20 mL). Stir for 3 hours, then add an aqueous solution (10 mL) of ammonium chloride (0.30 g), and extract the product with ether (3×10 mL). The resulting oil was dried overnight at 60° C. under high vacuum. A yellow solid (0.257 g, 83%) was obtained.
[0266] 1 H NMR(C6D6): δ8.24(m,1H),7.90(m,1H),7.64(m,1H),7.62(d,J=7.8Hz,1H),7.56(d,J=7.2Hz,1H),7 .26(m,3H),7.22(m,4H),7.11(m,5H),5.62(d,J=5.4Hz,1H,NCH),4.59(d,J=5.4Hz,1H,NH),3.31(se ptet,J=7.2Hz,1H,CH),2.74(m,2H),1.79(d,J=7.8Hz,2H),1.64(m,4H),1.54(m,4H),1.32(m,4H), 1.08(m,2H),1.03(d,J=6.6Hz,3H,CH3),1.00(m,1H),0.980(d,J=6.6Hz,3H,CH3),0.921(m,3H)ppm.
[0267] 13C NMR(C6D6): δ23.78,24.45,26.63,27.42,27.54,28.96,34.77,35.08,39.01,67.64,119.99,122.89,124.13,124.80,125.36,125.77,126. 08,126.46,126.56,126.71,127.58,128.55,129.35,131.84,134.64, 136.94,138.77,141.88,142.24,144.97,146.32,159.28,163.74ppm.
[0268] HRMS(EI): m / z calculated ([M + ]C 43 H 48 N2) 592.3817. Measured value: 592.3819
[0269] 2) Preparation of transition metal compounds
[0270] The Schlenk flask was filled with a toluene (1.5 g) solution of the ligand compound (0.150 g, 0.253 mmol) prepared above, and n-BuLi (0.17 mL, 1.6 M hexane solution, 0.27 mmol) was added dropwise at room temperature. Stir for 1 hour, then add HfCl4 (0.0814 g, 0.254 mmol) as a solid. The reaction mixture was heated at 100 ° C and stirred for 2 hours. After cooling, MeMgBr (0.29 mL, 3.1 M ether solution, 0.89 mmol) was added thereto, and stirred at room temperature overnight. After removing volatile substances with a vacuum tube, the product was extracted with toluene (1.5 g). The extract was obtained by filtration through diatomaceous earth. After removing the solvent by a vacuum tube, the residue was softened in hexane (2 mL) to obtain a yellow solid (0.128 g, 63%).
[0271] 1H NMR (C6D6): δ8.58(d,J=7.8Hz,1H),8.29(d,J=8.4Hz,1H),7.79(d,J=7.8Hz,1H),7.71(d,J=7.2Hz,1H),7.54(d,J=7.8Hz,1 H),7.46(m,1H),7.30(m,2H),7.15(m,3H),7.09(m,3H),6.88(t,J=7.8Hz,1H),6.62(d,J=8.4Hz,1H),6.48(s,1H,NCH),3.39 (m,1H),2.92(m,2H),2.15(d,J=13.8Hz,1H),2.10(d,J=13.8Hz,2H),1.80(m,2H),1.65(m,3H),1.29(m,6H),1.17(d,J=7.2 Hz,3H,CH3),1.07(m,3H),0.99(s,3H,HfCH3),0.95(m,2H),0.73(d,J=7.2Hz,3H,CH3),0.70(s,3H,HfCH3),0.23(m,1H)ppm.
[0272] 13 C NMR(C6D6): δ23.31,25.04,26.63,26.74,27.70,27.76,27.81,28.29,28.89,35.00,35. 66,36.62,37.02,38.13,40.88,62.53,67.00,77.27,119.30,120.30,124.29,125.52,1 25.60,125.97,126.95,127.06,127.73,129.91,130.00,130.09,130.85,134.36,135.8 0,140.73,140.89,144.02,145.12,146.31,146.38,146.49,164.46,170.79,206.40ppm.
[0273] Analytical calculation value (C 45 H 52 HfN2): C, 67.61; H, 6.56; N, 3.50%. Found: C, 67.98; H, 6.88; N, 3.19%.
[0274] (2) Preparation of organozinc compounds
[0275] 15.0g (98.3mmol) of 4-vinylbenzyl chloride and 2.628g (108.1mmol) of magnesium metal were added to 78ml of ether and stirred at 0°C for 1.0 hour, then filtered on diatomaceous earth to remove the excess magnesium. 19.2g (81.9mmol) of p-toluenesulfonyl-OCH2CH2Cl dissolved in 27ml of ether was added dropwise to the prepared 4-vinylbenzyl-magnesium chloride (4-vinylbenzyl-MgCl) Grignard reagent. Stir overnight, then filter on diatomaceous earth to remove magnesium chloride toluenesulfonate (MgCl(OTs)) as an insoluble salt. The filtered cake was washed three times with 70ml of hexane, and the solvent was removed by a rotary evaporator to obtain 14.2g of crude product. 43mg (3000ppm) of tert-butylcatechol was added as a free radical scavenger, and vacuum distillation was performed at 85°C under complete vacuum to obtain the compound shown in formula 8-4-1. As a result of measuring the weight of the obtained compound, the yield was 81 wt %, and the measured 1 H NMR and 13 C NMR spectrum.
[0276] [Formula 8-4-1]
[0277]
[0278] 1 H NMR (C6D6): δ7.20(d,J=8.4Hz,2H),6.88(d,J=8.4Hz,2H),6.61(dd,J=16,9.6Hz,1H,=CH),5.63(d,J=16Hz,1H,=CH2),5. 09 (d, J = 9.6 Hz, 1H, = CH2), 3.04 (t, J = 6.6 Hz, 2H, CH2), 2.42 (t, J = 6.6 Hz, 2H, CH2), 1.64 (quintet, J = 6.6 Hz, 2H, CH2Cl) ppm.
[0279] 13 C NMR (C6D6): δ32.61,34.12,44.07,113.13,126.74,128.97,135.99,137.11,140.63ppm.
[0280] Thereafter, 10.0 g (55.3 mmol) of the prepared compound (4-(3-chloropropyl) styrene) represented by the above formula 8-4-1 was dissolved in a mixed solvent of 20 ml toluene and 7.98 g (111 mmol) tetrahydrofuran (THF), and added dropwise at room temperature to a suspension of 2.02 g (83.0 mmol) magnesium powder stirred in 40 mL toluene. After stirring for 5.0 hours, a slight heat was gradually generated, and then the reaction mixture was filtered on diatomaceous earth to remove excess magnesium. To the filtrate, 6.94 g (55.3 mmol, 1 equivalent of Grignard reagent) of ethyl methoxide zinc produced by in-situ reaction of 6.83 g (55.3 mmol) diethyl zinc (Et2Zn) with 1.78 g (55.3 mmol) methanol in 30 ml toluene at room temperature for 1.0 hour was added. Thereafter, 60 ml toluene was added thereto, followed by stirring at room temperature for 1.0 hour, and then the solvent was removed using a high vacuum tube. Thereafter, 96 g of hexane was added thereto, and magnesium chloride methoxide (MgCl(OMe)) as an insoluble salt was removed on diatomaceous earth. The filtrate was stored at -30°C, thereby precipitating the compound represented by Formula 5-4 as a white crystalline solid. As a result of measuring the weight, the yield was 56 wt% (7.28 g), and the measured 1 H NMR and 13 C NMR.
[0281] [Formula 5-4]
[0282]
[0283] 1 H NMR (C6D6): δ7.24(d,J=7.8Hz,2H),6.90(d,J=7.8Hz,2H),6.64(dd,J=17,11Hz,1H,=CH),5.66(d,J=17Hz,1H,=CH2),5.1 1(d,J=11Hz,1H,=CH2),2.43(t,J=7.2Hz,2H,CH2),1.80(quintet,J=7.2Hz,2H,CH2),-0.19(t,J=7.2Hz,2H,CH2Zn)ppm.
[0284] 13 C NMR (C6D6): δ12.66, 28.82, 40.09, 113.15, 127.31, 129.23, 136.05, 137.10, 142.91ppm.
[0285] (3) Preparation of anionic polymerization initiator
[0286] (Trimethylsilyl)methyllithium (3.100 μmol, 291.9 mg) and N,N,N′,N″,N″-pentamethyldiethylenetriamine (3.100 μmol, 537.2 mg) were mixed with methylcyclohexane (20.7 g) and stirred at room temperature for 30 minutes to prepare an anionic polymerization initiator.
[0287] Preparation Example
[0288] Preparation Example 1
[0289] The Parr reactor (3.785 L) was dried under vacuum at 120° C. for 2 hours. A solution of MMAO (600 mg, 1000 μmol-Al) in methylcyclohexane (1200 g) was introduced into the reactor as a scavenger, and the mixture was stirred at 120° C. for 1 hour using a heating jacket, and then the solution was removed using a cannula.
[0290] The reactor was filled with methylcyclohexane (1200 g) containing MMAO (1000 μmol-Al) as a scavenger and trioctylaluminum (500 μmol) as an additive, and 1-hexene (560 g) as an α-olefin monomer, and then the temperature was set to 90° C. A solution of an organic zinc compound (3100 μmol) in methylcyclohexane (5 g) as a chain transfer agent was filled in the reactor, and then a solution containing [(C 18 H 37 )2N(H)Me] + [B(C6F5)4] - A solution of a transition metal compound (10 μmol-Hf) activated by a solution of (1.0 eq) in methylcyclohexane. The pressure in the reactor was maintained at 25 bar by opening the valve of the ethylene tank while the polymerization was carried out in the range of 90°C to 120°C for 40 minutes. After the polymerization, the ethylene gas was exhausted and the temperature of the reactor was then adjusted back to 90°C.
[0291] When the temperature reached 90°C, the anionic polymerization initiator prepared above (3100 μmol) was added. The temperature was maintained at 90°C for 30 minutes during stirring, and then styrene (56 g) was injected. The temperature was adjusted in the range of 90°C to 100°C using a heating jacket. The viscosity gradually increased and reached an almost invisible condition within 5 hours. An aliquot was taken for 1 H NMR spectroscopy was performed on the aliquot of 1 H NMR analysis confirmed the complete conversion of styrene. After the complete conversion of styrene, 2-ethylhexanoic acid and ethanol were injected continuously. The obtained polymer was dried in a vacuum oven at 80°C overnight to obtain a block copolymer.
[0292] Preparation Examples 2 to 4 and Comparative Preparation Examples 1 to 3
[0293] A block copolymer was obtained in the same manner as in Preparation Example 1, except that the types and contents of the transition metal compound, scavenger, organic zinc compound, α-olefin monomer, styrene, polymerization initiator and additives in Example 1 were changed to those described in Table 1.
[0294] However, in the case of Comparative Preparation Example 3, diethylzinc was used as the organic zinc compound instead of the organic zinc compound prepared above.
[0295] [Table 1]
[0296]
[0297] Examples and Comparative Examples
[0298] Example 1
[0299] To 50 parts by weight of the block copolymer prepared in the above Preparation Example 1, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0300] Example 2
[0301] 70 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added to 30 parts by weight of the block copolymer prepared in the above Preparation Example 1, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0302] Example 3
[0303] To 50 parts by weight of the block copolymer prepared in the above Preparation Example 2, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0304] Example 4
[0305] To 50 parts by weight of the block copolymer prepared in the above Preparation Example 3, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0306] Example 5
[0307] To 50 parts by weight of the block copolymer prepared in the above Preparation Example 4, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0308] Comparative Example 1
[0309] A resin composition compound was prepared in the same manner as in Example 1, except that in Example 1, when preparing the resin composition, G1645 manufactured by Kraton Co., which is a commercially available styrene-ethylene-butylene-styrene block copolymer (SEBS), was used instead of the block copolymer prepared in Preparation Example 1.
[0310] Comparative Example 2
[0311] A resin composition compound was prepared in the same manner as in Example 1, except that in Example 2, when preparing the resin composition, G1645 manufactured by Kraton Co., which is a commercially available styrene-ethylene-butylene-styrene block copolymer (SEBS), was used instead of the block copolymer prepared in Preparation Example 1.
[0312] Comparative Example 3
[0313] To 50 parts by weight of the block copolymer prepared in the above-mentioned comparative preparation example 1, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0314] Comparative Example 4
[0315] To 50 parts by weight of the block copolymer prepared in the above-mentioned comparative preparation example 2, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0316] Comparative Example 5
[0317] To 50 parts by weight of the block copolymer prepared in the above-mentioned comparative preparation example 3, 50 parts by weight of polypropylene (SFC-750D, manufactured by Lotte Chemical Co.) having a melt index (230° C., 2.16 kg) of 7.0 g / 10 min was added, and the mixture was compounded using a twin-screw extruder to prepare a resin composition compound. At this time, the temperature was 180° C. to 200° C., and the screw speed was 100 rpm.
[0318] Experimental example
[0319] For the resin compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 5, the shape of the domain, the size of the domain, and the distance between a plurality of domains were measured in the following manner and are shown in Table 2 below.
[0320] In addition, samples were prepared using the resin compositions prepared in Examples 1 to 5 and Comparative Examples 1 to 3 in the following manner, and the impact strength was measured and shown in Table 2 below.
[0321] * Small angle X-ray scattering (SAXS) analysis: The analysis was performed using a Xeuss 2.0SAXS / WAXS instrument manufactured by Xenocs Co. Specifically, the sample in the form of a sample was attached to a sample holder, and the corresponding sample was measured in a 2.5m SDD for 10800 seconds, and the air scattering intensity measured in the same time period was used as a background. The 2D MIDI images obtained from the experiment were averaged and converted to 1D images on a beam stop basis. Using this, each phase of the primary and secondary phases was assumed and modeled to obtain the shape of the domain, the size of the domain, and the distance between the domains.
[0322] * Low temperature impact strength (kgf·m / m): Each resin composition prepared in the examples and comparative examples was injected into a mold at 210°C for 10 seconds under a pressure of 6 bar and molded into a notch type with a size of 63.5 mm×10.16 mm×3.2 mm according to ASTM D256. At this time, the notch length of the prepared sample was 5 mm. For the prepared sample, the Charpy impact strength at low temperature (-50°C) was measured according to ASTMD256 by applying two pendulums 2025 using a model IT 504 impact tester manufactured by Tinius Olsen Co. The low temperature (-50°C) impact strength was determined as follows: the prepared sample was placed in a low temperature box set at -50°C, and the sample was exposed to -50°C for a period of more than 12 hours, and then the impact strength was measured within 3 seconds after the sample was taken out of the low temperature box.
[0323] [Table 2]
[0324]
[0325] As shown in Table 2, the resin compositions of Examples 1 to 5 prepared by using the block copolymers prepared in Preparation Examples 1 to 4 of the present invention have been shown to have excellent low-temperature impact strength because the shape of the domains is spherical and the size of the domains and the distance between multiple domains are satisfied, so it can be predicted that the resin compositions also have excellent room temperature impact strength.
[0326] On the other hand, the resin compositions of Comparative Examples 1 and 2 prepared by using G1645 manufactured by Kraton Co. (which is a commercially available styrene-ethylene-butylene-styrene block copolymer (SEBS)) instead of using the block copolymer prepared in Preparation Examples 1 to 4 of the present invention have been confirmed to have a cylindrical domain shape, a small domain size, and a narrow distance between multiple domains. As a result, it has been confirmed that Comparative Example 1 containing styrene-ethylene-butylene-styrene block copolymer (SEBS) in the same content as the content of the block copolymer prepared in Preparation Examples 1 to 4 in the resin compositions prepared in Examples 1 and 3 to 5 of the present invention has extremely poor low-temperature impact strength. As a result, it has also been confirmed that Comparative Example 2 containing styrene-ethylene-butylene-styrene block copolymer (SEBS) in the same content as the content of the block copolymer prepared in Preparation Example 1 in the resin composition prepared in Example 2 of the present invention has extremely poor low-temperature impact strength.
[0327] In addition, from Example 1, Examples 3 to 5 and Comparative Example 3, it has been confirmed that even if the shape of the domain is spherical and the distance between multiple domains is controlled, if the size of the domain is not large enough, the low-temperature impact strength will be reduced even if the content of the block copolymer is the same.
[0328] In addition, from Example 1, Examples 3 to 5 and Comparative Example 4, it has been confirmed that even if the shape of the domain is spherical and the size of the domain is controlled, if the distance between multiple domains is narrower than the range defined by the present invention, the low-temperature impact strength will be reduced even if the content of the block copolymer is the same.
[0329] In addition, from Example 1, Examples 3 to 5 and Comparative Example 5, it has been confirmed that even if the shape of the domain is spherical and the size of the domain is controlled, if the distance between multiple domains is wider than the range specified by the present invention, the low-temperature impact strength will be reduced even if the content of the block copolymer is the same.
[0330] Based on these results, it has been confirmed that by controlling the dispersibility of the block copolymer therein by controlling the size of the domain and the distance between multiple domains, the resin composition has excellent room temperature and low temperature impact strength. Therefore, it is confirmed that the resin composition of the present invention has excellent room temperature and low temperature impact resistance.
Claims
1. A resin composition comprising: a matrix region; and a plurality of domains dispersed in the matrix region, in, The matrix region comprises a polyolefin resin; The domain region comprises a block copolymer, and the block copolymer comprises an aromatic vinyl polymer block and an olefin polymer block; The size of the domain is 10nm to 15nm; The distance between the multiple domains is 20nm to 60nm.
2. The resin composition according to claim 1, wherein The domain has the shape of a sphere or an ellipsoid.
3. The resin composition according to claim 1, wherein The polyolefin resin is polypropylene.
4. The resin composition according to claim 1, wherein The olefin polymer block comprises ethylene monomer units and α-olefin monomer units.
5. The resin composition according to claim 1, wherein The olefin polymer block comprises ethylene monomer units and C3-C20 α-olefin monomer units.
6. The resin composition according to claim 4, wherein The α-olefin monomer is one or more selected from the group consisting of 1-propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, 4,4-dimethyl-1-pentene, 4,4-diethyl-1-hexene and 3,4-dimethyl-1-hexene.
7. The resin composition according to claim 1, wherein The resin composition includes the polyolefin-based resin in an amount of 40 to 80 wt % and the block copolymer in an amount of 20 to 60 wt %.
8. A method for preparing a resin composition, comprising: S10: polymerizing one or more olefin monomers by using a catalyst composition comprising a transition metal catalyst in the presence of a chain transfer agent to prepare an olefin polymer block intermediate; S20: In the presence of the olefin polymer block intermediate prepared in step S10, a polymerization initiator and an aromatic vinyl monomer are introduced and polymerized to prepare a block copolymer; and S30: blending the block copolymer obtained in step S20 with a polyolefin resin.
9. The method according to claim 8, wherein: The catalyst composition comprises an aluminoxane compound and a trialkylaluminum.
10. The method according to claim 9, wherein: The trialkylaluminum is trioctylaluminum.
11. The method according to claim 9, wherein: The catalyst composition comprises the aluminoxane compound and the trialkylaluminum in a molar ratio of 1:0.01 to 1:10.0.
Citation Information
Patent Citations
Organozinc compound including polyolefin-polystyrene block copolymers and method for manufacturing thereof
KR101657925B1
Overcurrent Protection by Depletion Mode MOSFET or JFET and Bi-Metallic Temperature Sensing Switch in Mini Circuit Breaker
KR1020220145764A